An integrated method for waviness simulation on large-size surface. (January 2015) - Sun, Yazhou; Chen, Wanqun; Liang, Yingchun; An, Chenhui; Chen, Guoda; Su, Hao
The surface waviness of the KH2 PO4 crystal has important influence on its optical performance, but it is difficult to simulate by the current simulation models. This article presents an integrated machining performance forecasting method, which considers the interaction between manufacturing process and machine tool and integrates the cutting simulation, machine tool dynamic performance simulation and the control system. The profile and waviness prediction on the large area are achieved by this method with short time and high accuracy. The machining trials on a fly cutting machine tool are carried out to demonstrate the effectiveness of the proposed approach.